BENTUK PENYAJIAN TARI JUBATA DALAM ACARA PERNIKAHAN SUKU DAYAK KANAYANT DI DESA SETANDUK KECAMATAN CAPKALA KABUPATEN BENGKAYANG - Oshin, Oshin; Ismunandar, Ismunandar; Fretisari, Imma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis analyses the form of the Jubata dance performance in the wedding of Kanayant Dayak Tribe in Setanduk Village, Capkala District of Bengkayang regency. The problems in this study are formulated as follows How is the form of Jubata dance performance in the wedding of Kanayant Dayak, contribute to the junior secondary education,describing the form of Jubata dance performance, and describing the contribution of the information regarding the Jubata Dance to the domain of junior high school education. This method in the form of qualitative with choreography approach. The informants this study are Arbinus, Orot, and Herman Toto. The data in this study of the interview and observation results, such as fieldnotes, photos, and videos. The techniques used in the observation, interview, and documentation. The data validated by using extended observation and triangulation. The data analysis, it was concluded that the Jubata dance consists of three movements. Other elements found in the performance are vertical, horizontal and circular floor design, contemporary group design, non-literary theme, proscenium stage, simple makeup, traditional dress, music accompaniment with agukng, tuma, tenga, soling, and poet, properties.The results of this study can be contributed as learning material in arts and cultural subjects in the 2013 curriculum.Â Keyword: Form of performance, JubataDance, Kanayant Dayak